Influence of Support Stiffness on Dynamic Characteristics of the Hydraulic Pipe Subjected to Basic Vibration - Wei Qu; Huailiang Zhang; Wei Li; Wenqian Sun; Lina Zhao; Haihui Ning (Shock and Vibration)
The basic vibration generated during the tunneling process of hard rock tunnel results in the change of the support stiffness of the hydraulic pipe, which causes the problem of reduction of pipe transmission efficiency. A transverse motion equation of the hydraulic pipe was established by correlating with Hamilton’s principle under basic vibration. In consideration of the fluid-structure interaction (FSI), the support was simplified as an equivalent and a spring. The bidirectional fluid-solid coupling analysis method was used to investigate dynamic characteristics of the pipeline under different support stiffness conditions. The finite element method (FEM) and the experimental analysis are applied to verify the proposed methodology. The numerical results show that the maximum displacement of the pipe decreases with the increase of the support stiffness; the maximum stress of the pipe decreases first and then increases with the increase of the support stiffness; the amplitude of the fluid pressure fluctuation at the outlet of the pipe increases with the increase of the support stiffness. But the fluid pressure fluctuation with the higher stiffness is first stable, which can indicate that the support stiffness can increase the damping of the pipe system. This study can get a significant access to the structural design of the pipeline under basic vibration.